동북아농정연구포럼 2006 활동보고서 - 어명근 (한국농촌경제연구원, 2006)
The Forum for Agricultural Policy Research in Northeast Asia (FANEA) was established jointly by the Korea Rural Economic Institute (KREI), the Chinese Academy of Agricultural Sciences (CAAS) and the Policy Research Institute under the Ministry of Agriculture, Forestry and Fisheries of Japan (PRIMAFF) in October 2003. This forum was launched to establish a collaborative relationship in agricultural research and related fields among Korea, China and Japan as part of their joint commitment to foster mutually beneficial research and development in the Northeast Asian countries. The major activities of FANEA in 2006 were the 4th FANEA International Symposium, joint studies between Korea and China, invitation seminars, homepage management, and other related activities. The 4th FANEA International Symposium was held under the theme of "Northeast Asian Agriculture under Economic Transition" from Sept. 4th through Sept. 6th in Seoul, Korea. In this symposium, hosted by the Korea Rural Economic Institute, nine papers dealing with three subordinate themes such as "Recent Agricultural Policy Reforms in Northeast Asia," "FTA Implications on Northeast Asian Agriculture," and "Emerging Issues in Recent Agricultural and Rural Development" were presented and debated by participants from the three countries. Also participating at the symposium were three observer institutes; the Japan International Research Center for Agricultural Sciences(JIRCAS), the Research Center for Rural Economy under the Ministry of Agriculture in China(RCRE), and Seoul National University. As a joint research project, FANEA conducted a study entitled "Study on China's Agricultural Policies Before and After Joining the WTO" with the Research Center for Rural Economy under the Ministry of Agriculture in China. FANEA has also hosted an invitation seminar entitled "Analysis on Changes and Adjustment of China's Agricultural Policies Before and After Joining the WTO." Besides, FANEA has performed several activities such as the attending of a seminar hosted by IAED/CAAS and the publishing of research materials, etc. Researchers: Myong-Keun Eor, Chung-Gil Chung, Keun-Soo Han, Hyun-Ju Lee, Jing-Hu Li E-mail address: myongeor@krei.re.kr